Estimation of the knowledge management model for performance measurement in university libraries. Issue 1 (20th August 2020) - Rafi, Muhammad; Jian Ming, Zheng; Ahmad, Khurshid
Abstract : Purpose: The study aims to expand the literature on evaluating the performance of professionals and academic libraries, rationalizing management and providing reliable services to the academic community. The performance assessment model covers the four components (management competence, professional experience, financial add/projects and library services) in the context of the knowledge management model. Design/methodology/approach: Based on quantitative data, the study defines a set of assumptions for testing the four components of performance evaluation within a knowledge management framework to develop appropriate and robust models for improving employee performance and library services. The structural equation model has been applied to sample data from 339 administrative librarians at 190 universities in Pakistan. Findings: Statistical evidence confirms that the applicability of the proposed performance-based model enhances management competence, makes accurate decisions, develops professional skills and strengthens human resource organization and knowledge management techniques in developing the efficiency of academic libraries. Practical implications: In the long term, academic leaders and policymakers value investment in the professional development of top library management as they participate in the decision-making process. Organizing training for service employees, supporting innovative research projects and providing library technology infrastructures ultimately improve academic performance and research when integrated into the knowledge management model. Originality/value: So far, comprehensive literature on performance and knowledge management has been published separately. However, based on the key data collected by senior library administrators using the structured research questionnaire, the comprehensive performance evaluation research based on a knowledge management model is innovative to improve academic library services and close the literature gap.